2001
DOI: 10.1017/s0952836901001625
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interspecific evaluation of predation by mammals and birds on the introduced red swamp crayfish Procambarus clarkii (Crustacea, Cambaridae) in a freshwater marsh (Portugal)

Abstract: The cray®sh Procambarus clarkii is an introduced species in Portugal, becoming a new available resource that has possibly changed local trophic relationships. The purpose of the present study was to understand better how a naã Ève assembly of predators reacted to a recent invader. Predation on P. clarkii by nine species of mammals (Order: Carnivora) and six species of birds (Order: Ciconiiformes) in a marsh area in Portugal, was surveyed through the collection of faeces and pellets over a 24-month period. Seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 30 publications
(34 reference statements)
4
58
2
Order By: Relevance
“…By contrast, P. leniusculus was present in spraints, particularly in the warmer months, despite previous work suggesting they were absent. The abundance of crayfish in spraints in summer was consistent with other European studies that have suggested invasive P. clarkii are a potentially important prey item (Beja, 1996), but with predation intensity low in winter (Correia, 2001). However, the proportion of crayfish encountered in other studies was considerably higher than here.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast, P. leniusculus was present in spraints, particularly in the warmer months, despite previous work suggesting they were absent. The abundance of crayfish in spraints in summer was consistent with other European studies that have suggested invasive P. clarkii are a potentially important prey item (Beja, 1996), but with predation intensity low in winter (Correia, 2001). However, the proportion of crayfish encountered in other studies was considerably higher than here.…”
Section: Introductionsupporting
confidence: 91%
“…For example, in Southern Europe, the invasive Louisiana Red Claw Crayfish Procambarus clarkii has been reported the main prey of several piscivorous species, including otters (e.g., Beja, 1996) and birds (Rodríguez et al, 2005). In Portugal, P. clarkii predation by otters was more intense in spring, summer and autumn than in winter, and was directed towards larger and heavier individuals (Correia, 2001). In Kenya, the diet of the African clawless otter Aonyx capensis has also been used to indicate the extent of P. clarkii dispersal (Ogada et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, by reducing aquatic plant biomass, crayfish reduce the availability of refuges to macro-invertebrates and fish, which may indirectly benefit higher trophic levels (such as predatory fish, birds and otters) by increasing prey vulnerability. Despite evidence suggesting that predation on crayfish increased juvenile otter survival (Ruiz-Olmo et al 2002) and that invasive red swamp crayfish were readily preyed upon by four species of mammalian carnivores and five species of ciconiiform birds (Correia 2001), there are currently too few data to properly assess the importance of crayfish as a dietary component for such predators. Our literature review did, however, suggest that crayfish can drive top-down trophic cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, invasive species often create novel trophic pathways, acting as both consumers and resources with, for example, invasive crayfish consuming both plant and animal material (Jackson et al 2014) and providing an abundant food resource for many taxa (e.g. Beja 1996;Correia 2001;Tablado et al 2010). In many European countries, invasive crayfish species have been widely introduced, with the signal crayfish (Pacifastacus leniusculus) usually being the most abundant (Kouba et al 2014), including in the UK (Jackson and Grey 2013).…”
Section: Introductionmentioning
confidence: 99%